IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY TERHADAP PEMAHAMAN SISWA DALAM MATERI FIQIH - Fadilah Lutfi; A. Faizul Mubarak (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Digital transformation has encouraged Islamic educational institutions to develop learning approaches that accommodate students' characteristics while preserving the pedagogical values of Islamic boarding schools (pesantren). Procedural Fiqh learning often encounters challenges because instructional practices remain predominantly conventional, limiting students' ability to visualize complex worship procedures effectively. This study aimed to analyze the implementation of Augmented Reality (AR) in Fiqh instruction and examine its influence on students' procedural understanding at Riyadul Ulum Islamic Boarding School. A qualitative approach with a phenomenological design was employed. Data were collected through classroom observations, in-depth interviews, and documentation involving teachers and students. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. Data trustworthiness was ensured through source and technique triangulation. The findings indicate that AR-based learning provides more concrete visualization of worship procedures, enhances student engagement, strengthens procedural understanding, and supports more accurate independent worship practices. The study also reveals that the effectiveness of AR implementation depends on the availability of digital infrastructure and teachers' technological competencies. Furthermore, this study proposes the concept of Immersive Fiqh Instruction as an innovative pedagogical approach that integrates Augmented Reality with the distinctive educational traditions of pesantren. These findings contribute to the advancement of technology-enhanced Islamic education while maintaining the authenticity of Islamic pedagogical values. ABSTRAK Transformasi digital mendorong lembaga pendidikan Islam untuk mengembangkan pembelajaran yang mampu mengakomodasi karakteristik peserta didik sekaligus mempertahankan nilai-nilai kepesantrenan. Materi Fiqih yang bersifat prosedural sering kali menghadapi kendala karena penyajiannya masih didominasi metode konvensional sehingga proses visualisasi gerakan ibadah belum optimal. Penelitian ini bertujuan menganalisis implementasi media Augmented Reality (AR) dalam pembelajaran Fiqih serta mengidentifikasi pengaruhnya terhadap pemahaman prosedural siswa di Pondok Pesantren Riyadul Ulum. Penelitian menggunakan pendekatan kualitatif dengan desain fenomenologi. Data dikumpulkan melalui observasi, wawancara mendalam, dan dokumentasi terhadap guru serta siswa, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña melalui tahapan kondensasi data, penyajian data, serta penarikan dan verifikasi kesimpulan. Keabsahan data diperkuat melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa penggunaan media AR mampu menghadirkan visualisasi prosedur ibadah secara lebih konkret, meningkatkan keterlibatan belajar siswa, mempermudah pemahaman tahapan ibadah, serta mendukung praktik ibadah yang lebih tepat. Implementasi media ini juga dipengaruhi oleh kesiapan infrastruktur digital dan kompetensi guru dalam mengelola pembelajaran berbasis teknologi. Penelitian ini menegaskan bahwa integrasi Augmented Reality dapat menjadi alternatif inovatif untuk memperkuat pembelajaran Fiqih di lingkungan pesantren tanpa menghilangkan karakteristik pedagogis dan nilai-nilai pendidikan Islam.